Regenerative Tourism, Stakeholder Behavior, And Sustainable Business Transformation: A Systematic Literature Review - Cahya Nova Kurniawan; Almer Rasyid; Khabiza Mirzha Azzahra; Lydia Ery Octalina; Oktavia Dewi Rizka Alam (UIN Raden Mas Said Surakarta, 2026)
This study aims to clarify the conceptual ambiguity of regenerative tourism and examine how it contributes to stakeholder behavioral transformation. Using a systematic literature review approach, this study analyzed 62 peer-reviewed articles through thematic synthesis involving open, axial, and selective coding. The findings show that regenerative tourism can be structured into four interrelated layers: ontological foundation, domain orientation, governance and system structure, and operational logic. The review also identifies six behavioral transformation pathways: experiential, cognitive-value, social-relational, institutional, technological, and empowerment pathways. Among these, empowerment emerges as a central mechanism linking governance structures to individual and collective agency. This study contributes to management and business literature by positioning regenerative tourism as a strategic framework for stakeholder engagement, destination governance, sustainable business models, and community-based value creation. The proposed framework offers a basis for future empirical testing and provides practical guidance for tourism managers, destination organizations, and policymakers seeking to design more inclusive and regenerative tourism practices.